The regulation of the right to occupational health during the health emergency due to COVID-19 in Mexico / La regulación del derecho a la salud en el trabajo en el marco de la emergencia sanitaria por la COVID-19 en México. - Salinas Ortiz, Issac Sebastián; Ascencio Romero, Ángel (Red de Investigación en Salud en el Trabajo; Vol. 5 Núm. 8 (2022): (Marzo-Agosto), 2022)
Derived from the current pandemic caused by the COVID-19 virus, the lack of efficiency, regulation, and protective legitimacy of the right to health is evident, not only in Mexico, but in many other countries, which is why the need arises to analyze the constitutional regulation of health. health at work, the health as a fundamental right from different perspectives, especially from its nature as a protected legal-constitutional right.